Seleção de motobombas para o setor sucroalcooleiro - Araujo, Priscila Jesus de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work has the purpose to explain how the sugar and alcohol sector works, detail all the processes which uses pumps and assist in the selection and specification of pumps attached with engines, that will make part in important industry processes in the manufacture of sugar and alcohol. A bibliographic revision about the working of sugar and alcohol sector and about pumps were made to help the analysis of a case. This case had the purpose to analyze the selected pumps that were part of a initial project of an industry which aimed a future expansion. The pumps that were selected to made part of the initial project were over dimensioned and were operating out of the best performance point, making the pumps inefficient because the expansion didn't happened. The solution was to select another pump with bigger performance and less power consumption to have a decrease in the energy consumption and in the operational costs of the industry and using the extra electric energy in the industry or selling it

Este trabalho tem por objetivo relatar como funciona uma usina sucroalcooleira, assim como detalhar todos os processos que utilizam bombas e auxiliar na seleção e especificação de bombas, acopladas com motores, que irão fazer parte dos processos industriais importantes na fabricação de açúcar e etanol. Uma revisão bibliográfica sobre funcionamento de usinas sucroalcooleiras e sobre bombas foi realizado para poder analisar um estudo de caso. Este teve como objetivo a análise das bombas selecionadas para fazerem parte de um projeto inicial de uma usina que futuramente visava expansão. As bombas que foram selecionadas para fazer parte do projeto estavam superdimensionadas e operando fora do ponto de melhor rendimento, se tornando ineficientes, visto que não houve expansão dessa usina. A solução foi selecionar outra bomba com maior rendimento e menos consumo de potência para que houvesse economia no consumo energético e no custo operacional, contribuindo com a sobra de energia elétrica na usina para venda ou para consumo próprio
Keywords: Energia eletrica - Conservação; Açucar - Usinas; Bombas hidraulicas; Bombas centrifugas; Energia - Fontes alternativas; Fire pumps